2020
DOI: 10.1186/s12886-020-01661-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid levels and risk of primary open angle glaucoma: a genetic study using Mendelian randomization

Abstract: Background The causal effects of plasma lipid concentrations and the risk of primary open angle glaucoma (POAG) are still unclear. Thus, the purpose of this study was to identify, applying a two-sample Mendelian randomization (MR) analysis, whether plasma lipid concentrations are causally associated with the risk of POAG. Methods Two-sample MR analysis of data from a genome-wide association study (GWAS) was performed to investigate the causal role of plasma lipid levels and POAG. A total of 185 independent s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Although glaucoma is not a characteristic of Tangier disease, GWAS for IOP and POAG have identified common variants in or near ABCA1 (rs2472493 and rs2487032) among more than 50 loci in Asian and European Caucasian populations [ 292 , 293 , 294 , 295 ]. However, while ABCA1 and other genes involved in lipid metabolism were found to be associated with IOP and POAG, a Mendelian randomization study did not find any evidence for a causal association between plasma lipid levels and POAG risk [ 296 ].…”
Section: Abca1 Age-related Macular Disease and Glaucomamentioning
confidence: 99%
“…Although glaucoma is not a characteristic of Tangier disease, GWAS for IOP and POAG have identified common variants in or near ABCA1 (rs2472493 and rs2487032) among more than 50 loci in Asian and European Caucasian populations [ 292 , 293 , 294 , 295 ]. However, while ABCA1 and other genes involved in lipid metabolism were found to be associated with IOP and POAG, a Mendelian randomization study did not find any evidence for a causal association between plasma lipid levels and POAG risk [ 296 ].…”
Section: Abca1 Age-related Macular Disease and Glaucomamentioning
confidence: 99%
“…Uroporphyrinogen decarboxylase encoded by UROD was an important element in hemoglobin synthesis, which is significantly up-regulated in POAG ( Figure 5D ). Studies have shown that patients with POAG have red blood cell backlog and high plasma specific viscosity ( Wang et al, 2004 ; Xu et al, 2020 ), indicating that the up-regulation of UROD may be an important cause of blood deformation in POAG patients. Further, we found that AL590666.2 and UROD have a strong correlation ( Figure 5E ), suggesting that AL590666.2 may be an important biomarker of POAG.…”
Section: Resultsmentioning
confidence: 99%
“…The relation between triglycerides and glaucoma has been conflicting, with studies showing an adverse association, 41 inverse association 42 and null association (Mendelian randomization study 43 ). A systematic review 44 of 12 studies reported a significantly higher risk of open-angle glaucoma with hyperlipidemia as well as hypertriglyceridemia (OR=1.42; 95%CI 1.04, 1.93; based on pooling of 4 studies).…”
Section: Discussionmentioning
confidence: 99%